1978
DOI: 10.1002/jrs.1250070511
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a few Raman lines of tryptophan

Abstract: The Raman spectrum of tryptophan has been observed in its neutral aqueous solution with 514.5, 488.0, 457.9, 363.8, and 257.3 nm excitation. The effects of N‐deuteration and 15N‐substitution of the indole ring on the Raman spectrum have been examined. A preliminary normal coordinate treatment of the indole ring has also been made. On the basis of these data, the vibrational mode and a possible origin of the Raman scattering intensity has been discussed for each of the 1623, 1555, 1436, 1344, 1016, 882, and 762… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 14 publications
3
51
0
Order By: Relevance
“…In this experiment 15‐N was incorporated into Hb by expressing the protein in bacteria grown on 15‐NH +4, and spectra were recorded in D 2 O in order to intensify the histidine signals12; a large 15‐N shift was seen for the 1407 cm −1 band that arises from protonated histidine residues 14. The 2 cm −1 downshift in 2×W18 is consistent with the 1 cm −1 shift, which was reported for the fundamental 15…”
Section: Resultssupporting
confidence: 90%
“…In this experiment 15‐N was incorporated into Hb by expressing the protein in bacteria grown on 15‐NH +4, and spectra were recorded in D 2 O in order to intensify the histidine signals12; a large 15‐N shift was seen for the 1407 cm −1 band that arises from protonated histidine residues 14. The 2 cm −1 downshift in 2×W18 is consistent with the 1 cm −1 shift, which was reported for the fundamental 15…”
Section: Resultssupporting
confidence: 90%
“…The 1555 cm −1 band is attributed to the degenerate pair of stretching vibrations of the benzene ring by Hirakawa et al [17] and can be found at 1556 cm −1 in our work. According to the work of Hirakawa et al, the strongly coupled benzene and pyrrole ring breathing vibrations give rise to two strong Raman bands located at 1016 and 762 cm −1 .…”
Section: L-tryptophanmentioning
confidence: 59%
“…Raman spectra has been used to define the differences in the environment around certain amino acid residues such as tryptophan or tyrosine 31–34. With the differences observed in degree of birefringence and morphology between fibers produced from 80% EtOH/water (Sample G) and AcOH (Sample P) we examined the Raman spectra of the generated fibers.…”
Section: Resultsmentioning
confidence: 99%